PERAN PEGADAIAN SYARIAH SEBAGAI SOLUSI DI TENGAH PANDEMI COVID-19 PADA MASYARAKAT INDONESIA - Hidayani (Program Studi Perbankan Syariah, 2020)
Sharia pawnshop is one of the BUMNs engaged in financial inclusion, PT Pegadaian (Persero) also supports the government???s programs in the welfare of the society. Sharia pawnshops as a solution that arise in the midst of public anxiety about the current uncertain situation. Sharia pawnshops are a tool that in principle is very helpful for the community. In this current era of globalization, people want things that are instant, practical, and easy to get. However, in real conditions, the community is not supported by basic competence. We all know that not everyone has a stable economic condition, and Pegadaian has become an alternative for most people when they are in urgent need of funds, especially in the current covid-19 situations. As for items that can be pawned, such as gold, gadgets, cameras, electronic goods and vehicles. The higher the value of the goods that you are pawning, the higher the loan amount you will get. The process is fast and there are not too many requirements and in minimal risk, this is what causes many people go to Pegadaian.